KONSTRUKSI PERUBAHAN CITRA PENYANYI DANGDUT PEREMPUAN INDONESIA DI TV REALITY SHOW - Robbikal Muntaha Meliala (Jurnal Akrab Juara, 2019)
Program of Dâ€™Academy 2 Indosiar is a talent search competition in television to produce qualified super star of â€œDangdutâ€ Singer. Appearance of Evi â€“ Masamba in this contest and her victory to be the first winner being own phenomenal to the society. Her uncommercial face and black skin would be caused of underestimate things in our society to choose Evi to be the winner. But as time goes by, the quality of inner and her humility have killed down all stigma. Mutual hard work from the indosiarâ€™s production team and commentator have succeed to construct new image of Evi to be beautiful, exotic and international looked singer. This program was broadcasted minimum 180 minutes and maximum 270 minutes to the audiences every Monday to Friday. Approaching to the final session, this program was broadcasted minimum 360 minutes and maximum 390 minutes to the audiences every Friday. Research Methodology : Descriptive Qualitative by Phenomenology Approached. Conclusion : Program of Dâ€™Academy 2 Indosiar has succeed to construct new image of Evi to be Beautiful Dangdut Singer, popular, humbled, fashionable, and qualified in â€œrockâ€ voice identity. Then, solidarity of youngster spirit from Masamba Teenager were raising up to support Evi by their own fan base. Masamba-South Sulawesi being famous district that Indonesia Government exploring for potential tourism object recently.